Prevention of Risky drinking among students at a Brazilian University - Simao, Maria Odete [UNESP]; Kerr-Corrêa, Florence [UNESP]; Smaira, Sumaia Inaty [UNESP]; Trinca, Luzia A. [UNESP]; Floripes, Tricia M. F. [UNESP]; Dalben, Ivete [UNESP]; Martins, Raul A. [UNESP]; Oliveira, Janaina B.; Cavariani, Mariana B. [UNESP]; Tucci, Adriana M. (Oxford University Press, 2008)
Aim: The aim of this paper was to compare the quantity and frequency of alcohol use and its associated negative consequences between two groups of college students who were identified as being risky drinkers. Subjects were randomly allocated in a clinical trial to intervention or control groups. Methods: Risky drinking use was defined as Alcohol Use Disorders Identification Test (AUDIT) >= 8 and/or Rutgers Alcohol Problem Index (RAPI) >= 5 problems in the previous year. Students who had undergone the Brief Alcohol Screening and Intervention for College Students (BASICS) (N = 145 at baseline; 142 at 12 months, and 103 at 24 months, loss of 29.7%) were compared with a control group (N = 121 at baseline; 121 at 12 months and 113 at 24 months, loss of 9.3%), the nonintervention group. Variables included drinking frequency, quantity and peak consumption, dependence assessment, and family and friends' abuse assessment. Results: Treated students at a 24-month follow-up decreased quantity of alcohol use per occasion and lowered AUDIT and RAPI scores. Conclusions: This is the first brief intervention work on risky drinking with college students in Brazil and the results are encouraging. However, it is difficult to conduct individual prevention strategies in a country where culture fosters heavy drinking through poor public policy on alcohol and lack of law enforcement.